Sustainable Livelihoods Approach: Alternative to Rural Development (Triyuga Academic Journal, 2021)
The purpose of this paper is to introduce the concept of sustainable livelihoods as a strategy for rural development. This paper explores how, under different contexts, sustainable livelihoods approach is useful on behalf of different livelihood strategies. This paper is basically based on secondary sources and interpretation is made as a content analysis method. People centered, holistic, dynamic, sustainable, micro-macro links etc. are the key principles of sustainable livelihoods approach. Policy makers are always concerned with the approaches to rural development in emerging country. This research also provides applied knowledge to fulfill the policy gap with reference to rural development. Further, it provides the guidelines to the decision makers, planners and academia, especially for the developing countries to understand the important lessons regarding rural development intervention.